Evaluating Mobile Mathematics Learning Application Success Using the DeLone–McLean Information Systems Success Model - Ferawati Ferawati; Lilis Stianingsih; Fiqih Hana Saputri; Rudi Setiyanto (SEAN Institute, 2026)
This study evaluates the success of the Math World mobile mathematics learning application implemented at SKh YKDW Tangerang using the DeLone and McLean Information Systems Success Model. A quantitative descriptive approach was employed involving 25 special education teachers as respondents. Data were collected through a questionnaire measuring six dimensions of information system success: System Quality, Information Quality, Service Quality, System Use, User Satisfaction, and Net Benefits. The data were analyzed using descriptive statistics based on percentage scores. The results indicate that the overall success level of the application reached 78.9%, which falls into the Good category. Among the six dimensions, User Satisfaction obtained the highest score (82.9%), followed by Information Quality (82.4%), while System Use recorded the lowest score (74.1%). The findings suggest that teachers perceive the Math World application as easy to use, providing accurate and relevant learning content that supports mathematics instruction for students with intellectual disabilities. However, improvements are still needed in system reliability, technical support responsiveness, and the integration of the application into regular classroom practice to maximize its educational benefits. Overall, the study concludes that Math World is an effective learning application with considerable potential to support inclusive mathematics education.